Neoadjuvant endocrine therapy for estrogen receptor positive breast cancer in an African setting - Molabe, Hunadi (Division of General Surgery, 2023)
Background Several studies have reported response rates for ER positive cancers on neoadjuvant endocrine therapy (NET), with lower toxicity compared to neoadjuvant chemotherapy (NCT). During the first wave of the COVID pandemic, clinician preference for NET increased significantly, buying time for hospital recovery before proceeding to surgery. To date, no studies have yet explicitly reported on the use of NET in an African context. Methods This study was a retrospective review, looking at breast cancer patients who received NET between 01 March 2019 to 31 December 2020 at Groote Schuur Hospital. Patients were included if they were female, older than 18 years, ER positive, and had a biopsy-proven breast cancer less than 50mm in size on clinical exam. Results There were 16 patients included in the study, of which all were female. The mean age was 59 years (range 41-75). When comparing the histological measurement to initial size on imaging, 7 patients had an excellent response to NET with tumours that decreased in size, whereas 9 patients had tumours that increased in size despite NET. There was no statistically significant difference between the two groups in terms of patient and pre-treatment tumour characteristics, pathological results, endocrine therapy, surgical therapy, or adjuvant oncological therapy. For the 9 patients who had progression on NET, the post resection median tumour size was more than double the pre-NET tumour size, as determined on imaging. Conclusion Until further studies can be performed in this setting, NET should be used with caution in situations where there will be a significant delay to surgery.